2007
DOI: 10.3390/12030654
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Products of Oxidation of Quercetin by Air Oxygenat Ambient Temperature

Abstract: Oxidation of quercetin by air oxygen takes place in water and aqueous ethanol solutions under mild conditions, namely in moderately-basic media (pH ∼ 8-10) at ambient temperature and in the absence of any radical initiators, without enzymatic catalysis or irradiation of the reaction media by light. The principal reaction products are typical of other oxidative degradation processes of quercetin, namely 3,4-dihydroxy-benzoic (protocatechuic) and 2,4,6-trihydroxybenzoic (phloroglucinic) acids, as well as the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 26 publications
3
71
0
2
Order By: Relevance
“…There is no doubt about quercetin, isoquercitrin, and quercitrin which are truly native plant components involved in the rutin metabolic pathway, but the origin of DTB, OTA, CDA, DDA, DPD, DBT, DBD, and DBOT is less certain. As shown in Dawidowicz et al (2016), they are formed during the heating of methanolic and methanol/water rutin solution, and they are also known as rutin and/or quercetin degradation products forming during their high-temperature treatment, UV irradiation, or exposure to other aggressive factors (Dubber et al 2005;Rohn et al 2007;Wang et al 2011;Zenkevich et al 2007;Zvezdanović et al 2012). The presented data show that some of them are formed during the heating of ethanolic and ethanol/water rutin solution.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…There is no doubt about quercetin, isoquercitrin, and quercitrin which are truly native plant components involved in the rutin metabolic pathway, but the origin of DTB, OTA, CDA, DDA, DPD, DBT, DBD, and DBOT is less certain. As shown in Dawidowicz et al (2016), they are formed during the heating of methanolic and methanol/water rutin solution, and they are also known as rutin and/or quercetin degradation products forming during their high-temperature treatment, UV irradiation, or exposure to other aggressive factors (Dubber et al 2005;Rohn et al 2007;Wang et al 2011;Zenkevich et al 2007;Zvezdanović et al 2012). The presented data show that some of them are formed during the heating of ethanolic and ethanol/water rutin solution.…”
Section: Resultsmentioning
confidence: 86%
“…2. All of them were identified and confirmed on the basis of the retention data of their standards, the PDA, MS 2 , HRMS, and literature data (Dubber et al 2005;Wang et al 2011;Zenkevich et al 2007;Zvezdanović et al 2012). The MS 2 and HRMS data for the identified compounds are collected in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1(A) shows that the methanolic rutin solution heated under reflux contains, besides the parent substance, 23 additional compounds formed as a result of the rutin transformation and degradation process. All of them were identified and confirmed on the basis of the retention data of their standards, the PDA, MS 2 , HRMS and literature data (Dubber et al 2005;Wang et al 2011;Zenkevich et al 2007;Zvezdanović et al 2012). The MS 2 and HRMS data for the identified compounds are collected in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2. Some of them were described in the literature as products of rutin and/or quercetin degradation resulting from high-temperature treatment, UV irradiation or the influence of aggressive environments: DTB, OTA, CDA, DDA, DBD, DBOT, DPD, quercetin, DBT, isoquercitrin and quercitrin (Dubber et al 2005;Rohn et al 2007;Wang et al 2011;Zenkevich et al 2007;Zvezdanović et al 2012). Yet our experiments have shown that these compounds are formed not only in aggressive conditions but also in the conditions typical for the extraction process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation